2011
DOI: 10.1590/s1516-35982011000400005
|View full text |Cite
|
Sign up to set email alerts
|

Yield, chemical composition and chlorophyll relative content of Tanzania and Mombaça grasses irrigated and fertilized with nitrogen after corn intercropping

Abstract: -It was evaluated the effect of the absence and of application of three nitrogen doses (50, 100 and 200 kg ha -1 of N) and four harvest times in the winter/spring season (from July to October) on dry mass yield (DMY), on the relative chlorophyll contents (ICF -leaf chlorophyll index) and on the contents of total digestible nutrients (TDN), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF) and lignin, and their respective correlations on Tanzania and Mombaça grasses after intercrop w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 16 publications
0
20
2
4
Order By: Relevance
“…Bernardino & Garcia (2009) reported that LI values below 30% limit the growth of both palisade and signal grasses. That period usually coincides with the critical period of competition for annual grain crops; therefore, if the grass shows rapid emergence and excessive initial growth, the application of a subdose of nicosulfuron is required (Pariz et al, 2011a), as it was done in the present study.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Bernardino & Garcia (2009) reported that LI values below 30% limit the growth of both palisade and signal grasses. That period usually coincides with the critical period of competition for annual grain crops; therefore, if the grass shows rapid emergence and excessive initial growth, the application of a subdose of nicosulfuron is required (Pariz et al, 2011a), as it was done in the present study.…”
Section: Resultsmentioning
confidence: 81%
“…The vast majority of current studies on grain crops, such as corn, sorghum, and soybean, intercropped with tropical forages in the ICLS conducted in the Brazilian Cerrado do not assess grazing by animals (Crusciol et al, 2011(Crusciol et al, , 2012Mateus et al, 2011;Pariz et al, 2011aPariz et al, , 2011bCosta et al, 2012). Therefore, researches with this approach and specifically with sheep and lambs (Ovis aries) are still essential in this context, since animal grazing with high stocking rates and inadequate management can reduce straw yield, besides affecting soil quality and crop productivity (Carvalho et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The highest TDMY and FDMY of Guinea grass cv. Tanzânia sown by broadcasting, on the day of maize sowing (Table 2) was due to the better emergence of this grass in relation to the other sowing methods, as well as to the higher yield potential compared to other forages, given by the better weather conditions of early spring ( Figure 1) (Pariz et al, 2011b). The lowest FDMY of Congo grass, sown in maize stage V4 without incorporation of seeds in the soil, can be explained by the shorter development time and lower plant density, requiring more time for tillering after maize harvest.…”
Section: Resultsmentioning
confidence: 99%
“…Factors such as these increase the likelihood of failure of fall crops ("safrinha" -second growing season), resulting in fallow agricultural areas during seven months of the year, compromising the success of no-till systems . In this context, integrated crop-livestock systems represent a viable alternative of year-round use of agricultural areas (Pariz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%